(untitled) (Research, Society and Development, 2021)
Dehydrated egg white is a product widely used in several applications, mainly in confectionery and bakery, however, when going through industrial processes it ends up losing some of its characteristics and functionalities. For that not to happen, research has been carried out looking for methods of dry thermal treatment that improve its characteristics and may also offer even greater microbiological safety. Thus, the objective of this work was to carry out a bibliographic review of the most recent research in this area, using Pubmed, Scientific Electronic Library Online (Scielo), and the CAPES periodical portal as databases and having as descriptors "clara de ovo desidratada" and "egg white powder". The research returned with a grand total of 4684 articles, of which 12 (from the CAPES platform) were related to the application of dry heat treatment. The results showed that the application of these technologies has been successful, however, only on a laboratory scale, and the economic viability for industrial application has not yet been evaluated.